Dr. Scott Trimas — Deep Plane Facelift — Jacksonville Beach - Trimas, Scott (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Scott Trimas, practicing in Jacksonville Beach, USA. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003314; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; usa; jacksonville beach